Clinical and social determinants of cardiovascular risk in a population with chronic noncommunicable diseases in Maicao, La Guajira, Colombia: 2024 - Paula Tatiana Angarita-Melo; Karen Panche-Castellanos; Víctor Zein Rizo-Tello; Ana Yibby Forero-Torres; Alexandra Porras-Ramírez (PLoS ONE, 2025)
Aim To determine the independent association and quantify the magnitude of influence of clinical and social determinants on the ten-year cardiovascular disease risk (estimated using the Framingham scale) in individuals diagnosed with arterial hypertension or type 2 diabetes mellitus in Maicao, La Guajira. Methods A cross-sectional analytical study was conducted among 273 adults enrolled in noncommunicable disease programs. Anthropometric, biochemical, and sociodemographic data were collected using standardized instruments. Multivariable logistic regression was used to identify and quantify factors associated with high cardiovascular disease risk (defined as 10% or greater Framingham score). Results The prevalence of high ten-year cardiovascular disease risk was 16.9%, being significantly higher in women (23.5%) compared to men (3.3%). The multivariable analysis quantified the influence of the determinants. Key clinical factors associated with the highest magnitude of risk were Type 2 Diabetes Mellitus (Adjusted Odds Ratio: 21.87) and High Blood Pressure (Adjusted Odds Ratio: 16.04). The independent effect of a social determinant, receiving a monthly salary, was also strongly associated with high risk (Adjusted Odds Ratio: 4.62). Conversely, being male and having normal High Density Lipoprotein cholesterol levels were identified as protective factors. Conclusion This study quantifies that, in addition to the strong influence of traditional clinical factors (T2DM and HBP), social determinants such as income-related work status exert a significant and independent effect on cardiovascular risk in this vulnerable population. The findings underscore the critical need for integrated public health strategies in Maicao, La Guajira, that not only target metabolic control but also effectively address structural social and gender inequalities to achieve a meaningful reduction in the cardiovascular disease burden.